Aplication of Family Centered Care on the Impact of hospitalization in Intensive Care Unit In Parents’ Perspective: literature Review - Staningsih Herlambang Kurniawati; Mariyam Mariyam; Dera Alfiyanti; Amin Samiasih (University of Muhammadiyah Semarang, 2022)
family-centred Care (FCC) is an effective intervention in reducing the impact of hospitalization. The aim of this literature review was to identify published research articles on the application of the FCC concept to the reduction of the impact of hospitalization in pediatric intensive care wards from the perspective of the parents. The literature review research took 14 journals from various databases published in 2015-2021. Searching for titles was obtained through identification and screening, entering inclusion criteria, so that 13 international journals and 1 national journal were obtained. The results of this study identified parental perspectives regarding the application of the core concepts of the FCC in reducing the impact of hospitalization, where each concept is accompanied by theme findings, for respect and dignity: a) the physical and cultural environment of the PICU, b) the expression of compassion and support from staff; sharing information: a) using understandable language, b) medical cycles, and c) satisfaction with communication; participation: a) parents as experts, b) how parents participate, c) environmental / staff impact on participation, and d) medical cycles; and Collaboration. This review reveals parents' reports that the implementation of the FCC concept in reducing the impact of hospitalization has not been fully fulfilled, as evidenced by the finding of positive and negative implementations related to the FCC concept.